2011
DOI: 10.4103/0970-1591.85451
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Mullerian duct syndrome with testicular seminoma: A report of two cases

Abstract: Persistent Mullerian duct syndrome is a rare form of male pseudohermaphroditism, characterized by the presence of the Mullerian duct structures in an otherwise phenotypically as well as genotypically normal male. We report two cases of males with cryptorchidism, and seminoma in the undescended abdominal testis along with Mullerian duct derivatives (uterus and fallopian tube).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 4 publications
0
2
0
2
Order By: Relevance
“…In the literature, sterility is indeed the rule but normal spermatogenesis has been reported. A thorough literature search found that 19% of reported adult patients fathered one or more children [Karimi-Nejad et al 1988;Farag, 1993;Berkmen, 1997;Aboutorabi et al, 2005;Liang et al, 2006;Jaka and Shankar, 2007;Prakash et al, 2009;Sichani et al, 2009;Inuganti et al, 2011;Kaore and Kaore, 2012;Kumar and Mohan, 2012;Kovachev et al, 2014;Sherwani et al, 2014;Agrawal and Kataria, 2015;Modi et al, 2015]. Farag et al [1993] reported an 11% proportion of fertile patients in Kuwait and neighboring populations.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…In the literature, sterility is indeed the rule but normal spermatogenesis has been reported. A thorough literature search found that 19% of reported adult patients fathered one or more children [Karimi-Nejad et al 1988;Farag, 1993;Berkmen, 1997;Aboutorabi et al, 2005;Liang et al, 2006;Jaka and Shankar, 2007;Prakash et al, 2009;Sichani et al, 2009;Inuganti et al, 2011;Kaore and Kaore, 2012;Kumar and Mohan, 2012;Kovachev et al, 2014;Sherwani et al, 2014;Agrawal and Kataria, 2015;Modi et al, 2015]. Farag et al [1993] reported an 11% proportion of fertile patients in Kuwait and neighboring populations.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…In the literature, sterility is indeed the rule, but normal spermatogenesis has also been reported. A thorough literature search found that 19% of reported adult patients fathered 1 or more children [Karimi-Nejad et al, 1988;Farag, 1993;Berkmen, 1997;Aboutorabi et al, 2005;Liang et al, 2006;Jaka and Shankar, 2007;Prakash et al, 2009;Sichani et al, 2009;Inuganti et al, 2011;Kaore and Kaore, 2012;Kumar and Mohan, 2012;Kovachev et al, 2014;Sherwani et al, 2014;Agrawal and Kataria, 2015;Modi et al, 2015]. Farag [1993] reported a proportion of 11% of fertile patients in Kuwait and neighboring populations.…”
Section: Infertilitymentioning
confidence: 99%
“…Abdominopelvik BT'de paraaortik, aortokaval alanı dolduran en büyüğü 27x35 mm boyutlarında, konglomerasyon gösteren lenfadenopatiler tespit edildi. Kemoterapiden 1 ay sonra çekilen flor-18 floradeoksiglukoz PET'de böbrek hilusu düzeyinden başlayarak paraaortik alanda iliak bifurkasyona kadar uzanan, aksiyel kesitlerde çapı 2,6 cm olarak ölçülen yumuşak doku dansitesinde minimal metabolik aktivite (SUVmax:3.04) tespit edildi (Resim 4). PET ile elde edilen bulgular kemoterapi sonrası inflamatuar süreç ile uyumlu olduğundan hastaya ek tedavi verilmeden izlemi uygun görüldü.…”
Section: Olgu Sunumuunclassified
“…Sıklıkla otozomal resesif geçmekle birlikte, X'e bağlı resesif kalıtımı da rapor edilmiştir. Erkek psö-dohermafroditizminin nadir bir formu olan bu sendroma transvers testiküler ektopi, herni uteri inguinalis ve çok nadir olarak testis veya Müller kanalı kalıntılarının tümörleri de eşlik edebilir 2 . Bu olgu sunumunda testis tümörlü PMKS'li bir hasta tartışıldı.…”
Section: Introductionunclassified